Age position, geodynamic specifics and paleomagnetism of intrusive complexes of the western coast of the Antarctic Peninsula - V.G. Bakhmutov; D. P. Gladkochub; V. V. Shpyra (Геофизический журнал, 2013)
New paleomagnetic and geochronological results on late Cretaceous-Paleogene intrusive and effusive complexes of the western part of the Antarctic Peninsula have been obtained. New isotopic dating "fills" regularly the temporal gap from 96 to 61 Ma demonstrating uninterrupted character of development of considered active margin from the phase of its origination to its collapse. For the most part of analyzed rocks from early associations of the Andian complex (96- 88 Ma) subductively-enriched lithospheric source can be definitely detected. For younger early Cenozoic products (about 60 Ma) a heterogeneous source, which appeared as a result of mixing of subductive and enriched asthenospheric components has been noticed. For uneven-aged groups of rocks the components of primary magnetization with directions being in a good agreement between them have been subdivided. Intrusive rocks along the western coast of the Antarctic Peninsula by both their age valuations and paleomagnetic estimations refer to the Cretaceous su-perchrone of normal polarity, while the rocks forming insular archipelagoes date back to Paleo-cene. New paleomagnetic poles for the late Cretaceous (for 112 and 85 Ma) and Paleocene (60 Ma) have been determined. The results provide evidence for the absence of considerable (within the limits of paleomagnetic method accuracy) displacements of the block of the Antarctic Peninsula from the East Antarctica during the last 100 Ma. It confirms the hypothesis that the opening of the Drake Straight in Oligocene occurred at the expense of the northward drift of the South America as to relatively stabile by its location Antarctic craton. Paleomagnetic results confirm the possibility of significant displacement of the South Shetland islands relative to the block of the Antarctic Peninsula in Paleogene-Eocene.